2021
DOI: 10.1097/dad.0000000000002092
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid Dedifferentiated Melanoma: The Diagnostic Role of Next-Generation Sequencing

Abstract: Sarcomatoid dedifferentiated melanoma (SDDM) represents a diagnostic challenge as this cutaneous spindle cell melanoma lacks expression of classic melanocytic markers including S100, SOX10, Melan-A, HMB45, and MITF. The expression of the emerging melanoma marker preferentially expressed antigen in melanoma (PRAME) in SDDM is largely unknown. In this article, a case of SDDM arising in association with a nodular melanoma is highlighted. A 65-year-old man presented with a several week history of an ulcerated lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…17,20 Rare, isolated reports have documented strong and diffuse nuclear staining for PRAME in dedifferentiated melanomas, but no comprehensive studies are available testing the diagnostic usefulness of PRAME in this setting. 14,20,21 Our experience with 9 primary dedifferentiated and 2 undifferentiated melanomas demonstrated that nuclear PRAME expression is strong and diffuse with a median combined score of 7 of 7. It is seen in both the AFX/PDS-like areas as well as those with aberrant differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…17,20 Rare, isolated reports have documented strong and diffuse nuclear staining for PRAME in dedifferentiated melanomas, but no comprehensive studies are available testing the diagnostic usefulness of PRAME in this setting. 14,20,21 Our experience with 9 primary dedifferentiated and 2 undifferentiated melanomas demonstrated that nuclear PRAME expression is strong and diffuse with a median combined score of 7 of 7. It is seen in both the AFX/PDS-like areas as well as those with aberrant differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…While a clinical history of a primary melanoma elsewhere is helpful in the metastatic setting, primary undifferentiated melanomas are likely underrecognized and underreported as their diagnosis relies entirely on mutational analysis with the detection of conventional melanoma driver mutations 1,4,18 . Primary dedifferentiated and undifferentiated melanomas closely resemble nonmelanocytic tumors, particularly AFX and PDS, and less commonly pleomorphic rhabdomyosarcoma or spindle cell squamous cell carcinoma (SCC) 3–8,11,13–15 . While primary cutaneous pleomorphic rhabdomyosarcoma is an exceptionally rare diagnosis, AFX, PDS, and spindle cell SCCs may appear morphologically and immunohistochemically inseparable from primary cutaneous dedifferentiated and undifferentiated melanomas presenting on chronically sun-damaged skin 5,19 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations